Communication Strategy In The Development Of Islamic Education In Al-Afifiyah Kopo Learning Park Bandung City - Iyad Suryadi; Hoerul Umam; rivaldy rivaldy (Universitas Muhammadiyah Enrekang, 2022)
This research is motivated by the large number of teenagers and children who lack interest in Islamic education, which has resulted in the Islamic education institution of the Al-Afifiyah learning center being quiet from activities, one of which is the environment of the Al-Afifiyah learning park. Many people who are in the Al-Afifiyah learning park are children who drop out of school, teenagers who are unemployed, and parents who do not educate properly. This study aims to analyze communication strategies in the development of Islamic education in the Al-Afifiyah Kopo Learning Park, Bandung City. This study uses Fred R. David's communication strategy theory with a qualitative descriptive approach method. Data collection techniques in this study were observation, interviews, and documentation. The data analysis techniques used were data reduction, data presentation, and drawing conclusions. In this study, there were three informants to obtain data from. The results of this study show that the communication strategy used by caregivers at the Al-Afifiyah Learning Park in Babakan Ciparay District, Cirangrang Village, and Bandung City is interpersonal communication using persuasive communication methods (repetition). Barriers to communication between caregivers of the Al-Afifiyah Learning Center in efforts to develop Islamic education in the Al-Afifiyah Learning Center are psycho-social human barriers.